2009
DOI: 10.3892/ijo_00000187
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells from bone marrow express tumor endothelial and stromal markers

Abstract: Abstract. Tumor development is a complex and dynamic process that involves malignant, vascular, and stromal cells. Endosialin is a tumor endothelial marker (TEM) present in the microvasculature and stroma of human tumors. Cancerassociated fibroblasts (CAF) have been implicated in promoting tumor development and have been associated with mesenchymal stem cells (MSC). Since stem/progenitor cells recruited either from bone marrow or residing in nearby tissues can contribute to pathological processes we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 36 publications
2
61
0
Order By: Relevance
“…On the one hand, these signaling pathways are functionally intact without the requirement of TEM-1 expression in most cells. On the other hand, TEM-1 expression seems to be required in some precursor cell types: mural cells (pericytes, which could be viewed as precursors of vascular smooth muscle cells), 12 endothelial progenitor cells, 31 mesenchymal stem cells (MSCs) 12,32 and stromal fibroblasts (with the potential to differentiate into many different cell types). 12 In the developing mouse embryo both stromal fibroblasts and perivascular cells were found to express elevated levels of TEM-1.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, these signaling pathways are functionally intact without the requirement of TEM-1 expression in most cells. On the other hand, TEM-1 expression seems to be required in some precursor cell types: mural cells (pericytes, which could be viewed as precursors of vascular smooth muscle cells), 12 endothelial progenitor cells, 31 mesenchymal stem cells (MSCs) 12,32 and stromal fibroblasts (with the potential to differentiate into many different cell types). 12 In the developing mouse embryo both stromal fibroblasts and perivascular cells were found to express elevated levels of TEM-1.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed that CD248-expressing cells proliferate in vivo. Taken together, we suggest that CD248 1 stroma is required for full pLN expansion by increasing proliferation of mesenchymal cells in the medulla and capsule of pLN.It has recently been shown that CD248 is expressed on human bone marrow-derived mesenchymal stem cells (MSC) [19]. As such cells have been suggested to play a role in tissue remodelling and repair [20], we were interested to see whether CD248 played a role in regulating differentiation of mouse mesenchymal cells.…”
mentioning
confidence: 99%
“…It has recently been shown that CD248 is expressed on human bone marrow-derived mesenchymal stem cells (MSC) [19]. As such cells have been suggested to play a role in tissue remodelling and repair [20], we were interested to see whether CD248 played a role in regulating differentiation of mouse mesenchymal cells.…”
mentioning
confidence: 99%
“…In contrast to the bene icial effects, however, adverse effects of MSCs on multiple tumour models have also been reported. It has been found that in tumour tissues MSCs could differentiate into myo ibroblastslike cells, which have been proven to play a crucial role in tumour promotion through multiple mechanisms, including promotion of tumour stroma remodelling and tumour invasiveness 30 . It was demonstrated that when exposed to a tumourconditioned medium over a long period MSCs gained a myo ibroblastic phenotype as evidenced by an expression of carcinoma-associated markers, including stroma-derived factor-1 (SDF-1), α-SMA and ibroblast surface protein 31 .…”
Section: Mscs Therapy In Liver Cancermentioning
confidence: 99%